2014
DOI: 10.3233/jad-131892
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Nutritional Status Between Very Mild Alzheimer's Disease Patients and Healthy Controls

Abstract: In non-malnourished patients with very mild AD, lower levels of some micronutrients, a different fatty acid profile in erythrocyte membranes and a slightly but significantly lower MNA screening score were observed. This suggests that subtle differences in nutrient status are present already in a very early stage of AD and in the absence of protein/energy malnutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 64 publications
6
56
1
1
Order By: Relevance
“…Of the remaining 66, 51 irrelevant studies were excluded by reviewing the title and abstracts. A total of 15 full text articles [7][8][9][10][11][12][13][14][15][16][17][18][20][21][22] were thoroughly reviewed for their inclusion. Of these, 3 duplicate articles were excluded [20][21][22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the remaining 66, 51 irrelevant studies were excluded by reviewing the title and abstracts. A total of 15 full text articles [7][8][9][10][11][12][13][14][15][16][17][18][20][21][22] were thoroughly reviewed for their inclusion. Of these, 3 duplicate articles were excluded [20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…As an antioxidant it protects OS mediated cell damage through a series of selenoproteins mainly glutathione peroxidase (GPx) and selenoprotein P [2,6]. The results of the available studies on selenium levels in AD are inconsistent [7][8][9][10][11][12][13][14][15][16][17][18]. While some studies have shown that AD patients have lower selenium levels [7,9,10,14,16,17], others [8,[11][12][13]15,18] have contrariwise reported an increased or no change.…”
Section: Introductionmentioning
confidence: 91%
“…The rate of malnutrition and malnutrition risk is very high in patients with dementia. It is reported that the onset of poor nutrition may be even before classical symptoms of dementia (1,2). It is crucial to screen these patients for malnutrition because poor nutrition is associated not only with a faster progression of dementia but also with adverse health problems (2,6,9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Even the early stage of AD is associated with certain micronutrient deficiencies and a worse nutritional state compared to healthy subjects (1). Furthermore, weight loss is associated with a rapid cognitive decline in community-dwelling patients with AD (2).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, selenate treatment was shown to positively alter the phosphorylation status of key proteins involved in oxidative stress, energy metabolism and protein degradation in cellular model of AD as indicated in broad phosphoproteomics study. Apart from playing important roles in regulation of redox homeostasis, ATP generation, and misfolded proteins clearance, selenate-treatment also resulted in reduction of homocysteine, phospho-tau as well as Aβ levels [129].…”
Section: Alzheimer's Diseasementioning
confidence: 99%